Fluorescence characteristics of associates of eosin Y with cationic surfactants in water-micellar systems of Triton X-100 - Klovak, V.O.; Nechpai, L.O.; Lelyushok, S.A.; Kulichenko, S.A.; Zaporozhets, O.A. (Reports of the National Academy of Sciences of Ukraine, 2019)
The influence of cationic, nonionic surfactants and their mixtures on the fluorescence characteristics of eosin Y has been studied. The studies have been carried out at pH 10, under conditions of the existence of a dye in the form of a dianion. The dependences of the fluorescence intensity of eosin Y on the concentration of cationic surfactants (n = 14 ÷ 16) have been characterized by the presence of minima in the area of the formation of stoichiometric associates eosin : cationic surfactant = 1 : 2. With a further increase in the concentration of cationic surfactants, the intensity has reached the “plateau”. In contrast, the molecular emission maximum in the area of the formation of stoichiometric associatives has been reached with the addition of short-chain cationic surfactants to the dye solution. The difference in the nature of concentration dependences is explained by the different nature of the formed associates. The study of the effect of the hydrocarbon radical length on the intensity of the fluorescence of the dye has been carried out at two concentrations of cationic surfactants: under condition of the formation of stoichiometric associates of the dye with cationic surfactant and in the region of the micellar concentrations of cationic surfactants. The nature of the dependences of the fluorescence intensity of eosin Y on the concentration of cationic surfactants enables one to register the processes of formation and aggregation of stoichiometric associates of eosin Y with cationic surfactants, their dispersion through the stage of formation of substoichiometric associates and solubilization in micelles with an excess of cationic surfactants. The decrease of the fluorescence intensity of solutions of aggregated hydrophobic associates and, conversely, the increase of the fluorescence intensity of solubilized forms have been established. The difference in the nature of the associates of eosin Y with hydrophobic and moderately hydrophobic cationic surfactants has been leveled in the presence of a nonionic surfactant Triton X-100. The intensity of the fluorescence of eosin Y, depending on the number of carbon atoms in the hydrocarbon radical of halide alkyl pyridinium in the presence of a nonionic surfactant, has been closed in value. Namely, the leveling effect of the nonionic surfactant on the fluorescence characteristics of the associates of eosin Y with cationic surfactants, which provides the ability to identify organic cations of different hydrophobicities, has been observed.